PENGARUH LEVERAGE, PROFITABILITY, DAN FAKTOR LAINNYA TERHADAP TAX AVOIDANCE - Ramadhan, Rian Zaki; Putri, Ade Hanifa (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study aims to obtain empirical evidence and examine the influence of the independent variables leverage, profitability, sales growth, firm age, firm size, and capital intensity on tax avoidance. By analyzing these factors, hopefully this research can provide new insights into the factors that influence tax avoidance in emerging markets.The research subjects are companies in the consumer cyclicals and consumer non-cyclicals sectors listed on the Indonesia Stock Exchange (IDX) during the period of 2020-2022.The sampling method used in this study is purposive sampling, which resulted in 61 companies meeting the criteria, providing a total of 183 data points for the analysis. This research employs multiple regression analysis. The findings indicate that leverage, profitability, sales growth, and firm size have an impact on tax avoidance, while firm age and capital intensity do not influence tax avoidance.